The Relationship Between Family Support, Information Sources, and the Role of Health Workers and Colostrum Feeding Behavior in Newborns at Basarang Community Health Center 2025 - Yusiana Yusiana; Rifzul Maulina (Jurnal Rumpun Ilmu Kesehatan, 2025)
Introduction: Colostrum is a part of breast milk (ASI) that has the characteristics of a yellowish liquid that comes out on the first to third day after giving birth. Colostrum contains many immune substances 10-17 times more than mature milk, so it is very good to be given because it functions to form baby antibodies. Objective: To determine maternal knowledge, family support relationships, sources of information, the role of health workers, maternal behavior, and how to provide colostrum by giving colostrum to newborns at Basarang Health Center in 2025. Method: The research method used is descriptive with a Sectional Study approach. The sample in this study was postpartum mothers on days 1-4, with a total of 30 samples. This sample was taken using a purposive sampling method, and the measuring instrument used was a questionnaire. Results: This study found a relationship between colostrum provision and family support (p = 0.029), sources of information (p = 0.003), and behavior (p = 0.000). While there was no significance of maternal knowledge (p=0.0966), the role of health workers (p=0.836), and how to give colostrum (p=0.997) with colostrum. Conclusion: There is a relationship between family support, sources of information, and behavior with colostrum giving, and there is no relationship between maternal knowledge, the role of health workers, and how to give colostrum with colostrum giving.